An investigation on the effectiveness of centralisation on the financial performance of Cimas medical laboratories - Mazanhi, Joel (Midlands State University, 2017)
The research was undertaken to investigate the effectiveness of centralisation on the financial performance of Cimas Medical Laboratories. The objectives sought to find out the effects of centralisation of authority on the financial performance of an organisation. Descriptive design was used in this study and the presentation, analysis and interpretation of data was done using tables, charts and graphs. A sample of 30 participants was used being drawn from the population and management of employees of 48 participants. Data gathering methods used include questionnaires and interviews and these provided data for the research. This was presented in graphs, tables and charts as also expressed as percentages. The ethical issues were also considered to maintain confidentiality. No disclosure should be made on the data received from the research subjects but only for the intended use which is for academic purposes. It was found that centralisation has more of negative effects which hinder the operations of an organisation as compared to the positive effects. These hindrances in the operation of an organisation negatively affect the financial performance of an organisation. These negative effects among others include increases in costs, running out of inventory and delays in performance of works. The recommendations made centred mostly on the delegation of authority, which is the decentralisation of decision making to lower management levels